Where Are You From? Socio-Spatial Identities in Partner Choice and The Transition To Adulthood in Yogyakarta, Indonesia - Ariane Juliana Utomo; Oki Rahadianto Sutopo (Populasi, 2026)
With development and social change, spatial homogamy—the tendency to marry someone from the same area of origin—is expected to decline. In Indonesia, this phenomenon remains under-examined, and little is known about how young adults perceive it. This article explores patterns of spatial homogamy and the extent to which socio-spatial identities shape partner choice and marriage aspirations among young people in Yogyakarta, Indonesia. Using the 2010 Population Census, we identify patterns and correlates of spatial homogamy defined as marriage within the same birth district. Guided by these results, we selected two contrasting sites with high and low homogamy levels and conducted in‑depth interviews and focus groups with 34 young people (aged 16–30) in 2019. Spatial homogamy was lowest in Yogyakarta City (39.5% of married couples) and highest in rural Gunung Kidul (89.9%). Younger age, higher education, and urban residence were associated with a lower likelihood of marrying within one’s district. Rural youth framed mobility as a way to move beyond marrying someone from the same village, while urban participants prioritised shared values and visions over geographic origin. Still, socio-spatial identities influenced partner choice across both contexts. Socio-spatial identities continue to shape partner choice and marriage aspirations even as education and mobility diversify partner pools, weakening—but not erasing— locality-based ties and preferences.